2020
DOI: 10.7759/cureus.8612
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Feedback Program Evaluation in CIMS Multan, Pakistan

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…21 All these findings are in line with our study results where the mentors are willing to be role models for a positive behavior change in mentees but also impart meaning at work. This cordial relationship can therefore add to personal and professional development as well as emotional well being of mentees as has been recognized in a national study 22 .…”
Section: A H E a D O F P R I N Tmentioning
confidence: 81%
“…21 All these findings are in line with our study results where the mentors are willing to be role models for a positive behavior change in mentees but also impart meaning at work. This cordial relationship can therefore add to personal and professional development as well as emotional well being of mentees as has been recognized in a national study 22 .…”
Section: A H E a D O F P R I N Tmentioning
confidence: 81%
“…Highlighting the option to post anonymously and assure students that 'negative' comment will have no impact on their future teaching or assessment is imperative. Providing guidance on how to formulate feedback to teachers may also empower students [14,19].…”
Section: Power Imbalance Between Student and Teachermentioning
confidence: 99%
“…When constructed well, online tools offer a simple, cost-effective method of collecting feedback from large groups of learners [9]. A study by Shabbir et al demonstrated a significant increase in the response rate with use of online form compared a paper evaluation form [14]. Online feedback is not a new approach but, to ensure evaluations are valid, responses must be collected at appropriate times, requested throughout teaching programmes, and returned with an adequate response rate [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Institutions all over the world allocate resources to improve the faculty evaluation system; in Pakistan, most medical institutions have developed state-of-the-art systems to evaluate the quality of teaching with an intent to enhance the learning environment [6][7][8]. However, the inability of these evaluation systems to obtain real-time feed with assurance of complete anonymity for students might affect the quality of evaluation.…”
Section: Introductionmentioning
confidence: 99%